2006
DOI: 10.1002/jcb.21123
|View full text |Cite
|
Sign up to set email alerts
|

A role for PLCγ2 in platelet activation by homocysteine

Abstract: The aim of this study was to examine the homocysteine effect on phospholipase Cgamma2 (PLCgamma2) activation and to investigate the signaling pathway involved. We found that homocysteine stimulated the tyrosine phosphorylation and activation of platelet PLCgamma2. The tyrosine kinases p60src and p72syk appeared to be involved upstream. Reactive oxygen species were increased in homocysteine treated platelets. Likely oxidative stress could prime the non receptor-mediated tyrosine kinase p60src, inducing phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 47 publications
(61 reference statements)
2
11
0
Order By: Relevance
“…The concentrations of Hcy and HTL were similar to those used in studies of other investigators [17,18]. The present study demonstrated that lipid peroxidation (measured using a colorimetric method dedicated to TBARS) of human plasma treated with the reduced form of Hcy and its thiolactone was distinctly increased compared with control (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…The concentrations of Hcy and HTL were similar to those used in studies of other investigators [17,18]. The present study demonstrated that lipid peroxidation (measured using a colorimetric method dedicated to TBARS) of human plasma treated with the reduced form of Hcy and its thiolactone was distinctly increased compared with control (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…The concentrations of Hcys and HTL were similar to those used in studies of other investigators [37]. Here, we present evidences that not only the reduced form of Hcys, but also HTL (at lower concentrations than Hcys) induced platelet apoptosis in vitro (Figures 1-4).…”
Section: Discussionsupporting
confidence: 73%
“…***P < 0.001 and **P < 0.01 compared with 5.5 mM glucose; # P < 0.05 compared with 15 mM glucose; § § § P < 0.001 compared with baseline. let activation (17). As shown in Figure 7A, under both NG and HG conditions, the phosphorylation of PLCγ2 was significantly enhanced upon collagen-induced platelet aggregation.…”
Section: Figurementioning
confidence: 86%